Aesthetic and family frames in the online sharing of children's birthday photos. (May 2014) - Wang, Li; Alasuutari, Pertti; Aro, Jari
This article reports on a social semiotic investigation into children's birthday photo sharing and textual interaction in the public photo sharing websiteFlickr.com ; the analysis shows that the aesthetic frame becomes more prominent in the online context. In other words, people share their family photos as a form of self-expression, and that can be seen in the semiotic organization of the verbal and visual texts they publish. However, the aesthetic frame is often entwined with the family frame both in the postings of the image publishers and in the comments that the photos gather. It could have been assumed that the aesthetic frame assumes a particularly dominant position on Flickr, which as a social media site specializes in publishing photographs and discussing their qualities. Since the family frame nevertheless retains an important role on Flickr, it can be expected that the same is true of more general social media services such as Facebook.